1998
DOI: 10.1063/1.120569
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen plasma annealing for low temperature Ta2O5 films

Abstract: A low temperature oxygen/nitrogen plasma process is reported that substantially reduces leakage currents in chemical vapor deposited (CVD) and physical vapor deposited (PVD) films of tantalum oxide. We show that a combination of nitrogen and oxygen in a remote downstream microwave plasma source reduces leakage currents in CVD films of tantalum oxide and also reduces trap densities as measured by charge pumping. The as deposited CVD films show a high level of photoluminescence that is substantially lowered by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(40 citation statements)
references
References 5 publications
1
39
0
Order By: Relevance
“…As one of the alternative gate dielectric materials, tantalum pentoxide (Ta 2 O 5 ) has been studied extensively in applications such as storage capacitors in dynamic random access memory (DRAM), gate oxide in field effect transistors (FET) due to its high permittivity, high refractive index, excellent step coverage, and tolerable dielectric strength [1][2][3]. Recently, promising applications of Ta promoted even greater interests [4]. Although much research effort has been devoted to the structural and electrical properties of the materials, as-deposited Ta 2 O 5 thin films still suffer from the crystallization difficulty and poor electrical properties [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the alternative gate dielectric materials, tantalum pentoxide (Ta 2 O 5 ) has been studied extensively in applications such as storage capacitors in dynamic random access memory (DRAM), gate oxide in field effect transistors (FET) due to its high permittivity, high refractive index, excellent step coverage, and tolerable dielectric strength [1][2][3]. Recently, promising applications of Ta promoted even greater interests [4]. Although much research effort has been devoted to the structural and electrical properties of the materials, as-deposited Ta 2 O 5 thin films still suffer from the crystallization difficulty and poor electrical properties [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] Oxide transistors based on high -k dielectrics have received the most attention and a number of high mobility, low-voltage devices have been demonstrated. [ 15 , 17 ] The high -k materials studied to date include transition metal oxides such as Ta 2 O 5 , TiO 2 , [19][20][21][22] ZrO 2 , [23][24][25][26] Al 2 O 3 , [ 27 ] HfO 2 , [ 28 ] and silicates, [ 29 ] as well as ferroelectric materials such as Pb(Zr,Ti) O 3 and (Ba,Sr)TiO 3 . [ 30 , 31 ] Among these, ZrO 2 and HfO 2 are the most extensively studied dielectrics and are widely considered to be excellent candidates because of their relatively high dielectric constants, good thermal stability, and large band gaps.…”
mentioning
confidence: 99%
“…Prior to application of sputter-deposited films it is necessary to understand the relation between microstructure, growth conditions, and resulting electrical and optical properties. A through optical study of such microstructure related effects was shown previously for magnetron sputtered boron nitride thin films [18][19][20][21] Tantalum oxide films ͑TOF͒ have been grown by a large variety of physical vapor deposition and chemical vapor deposition ͑CVD͒ processes, including ion beam sputtering, 22,23 magnetron sputtering, 2,7,9,24 ͑low temperature͒ thermal oxidation, 9,25 anodization, 26 ion plating, 1,27 electronbeam evaporation, 4,27 laser ablation, 28,29 low pressure CVD, 14,30 photo-CVD, 31,32 atomic layer deposition, 33 and plasma-enhanced CVD. 12,16,34 A metalorganic solution deposition technique 6 was also used to grow TOF.…”
Section: Introductionmentioning
confidence: 99%